VENTILATION LEGISLATION (Tufts Archival Research Center, 2007)
Draft; Illegible/Difficult to Read; Confidential; Draft of Ventilation Legislation listing: assumptions concerning ventilation legislation, objectives for ventilation legislation, and strategies and goals for the legislation. Emphasizes the need to recruit as many supportive groups and unions as possible. Lists possible corporations and associations that could be considered as allies.